Highest Ground - Ferguson, Rodney (Cosmos and History: The Journal of Natural and Social Philosophy, 2015)
I believe that life, consciousness, and free will are intertwined. Our current scientific efforts at understanding them are undermined by studying these as discrete phenomena. It is my contention that although science, particularly quantum physics and biology, has made some strides in how the brain may work; however, this effort will not yield the desired outcome. Only by raising the consciousness level of all humans will we begin to fully understand human consciousness. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->